A study of PT, APTT, fibrinogen and urinary protein-creatinine ratio in paediatric patients with nephrotic syndrome - Rani, A. Sujatha (International Journal of Contemporary Pediatrics, 2017)
Background: Nephrotic Syndrome (NS) is very common in children. The typical laboratory finding is high urinary protein creatinine ratio. Apart from it low serum albumin, high cholesterol contribute to hyper coagulable states. Due to this the risk of thromboembolism in both arterial and venous circulation is significant in children and adults. Patients at risk for thromboembolism traditionally have to be screened by ventilation/perfusion scans and Dopplers for the definitive diagnosis of thromboembolic disease. There are several studies performed on adult nephrotic syndrome and thromboembolic events in them worldwide. We wanted to look for simple, affordable tests, that can be performed even when state of the art technology is not available, and can point towards at risk thromboembolic patients. Methods: The study was conducted in 17 nephrotic syndrome children in active disease, 13 nephrotic syndrome children in remission and 15 healthy children as controls, all between 4-14 years age group. Study included both male and female children. Results: Our results revealed prolonged. APTT in NS with active disease when compared to remission and control groups. High fibrinogen levels in relapse group indicated hypercoagulative state, along with routine parameters such as high cholesterol and low albumin. Both relapse and remission groups had proteinuria, with very high P/C ratio in relapse group, indicating at risk group for thromboembolic complications along with basic coagulation parameters. Conclusion: We suggest that when there are indications of hypercoagulable state antiplatelet drugs such as a low dose aspirin 75 mg or low dose warfarin may be given as prophylactic treatment for thromboembolic disease.